The global nutrition landscape: Assessing progress - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
AS DISCUSSED IN CHAPTER 1, SETTING TARGETS IS ONE MANIFESTATION OF POLITICAL COMMITMENT. COUNTRIES HAVE ALREADY MADE A SERIES OF COMMITMENTS TO ATTAIN global nutrition targets by 2025 (Panel 2.1). For maternal, infant, and young child nutrition, the 2012 World Health Assembly (WHA) set six targets for 2025. The Global Nutrition Report tracks five of these.1 The WHA also agreed on nine noncommunicable disease (NCD) targets, one of which—“Halt the rise in diabetes and obesity”—is tracked in this report via three indicators. In all, we use eight nutrition status indicators to track six of the targets.